Pizwak, A Famous Dari Poet - Hussain, Yousaf (sourcecoder, 2024)
Abdu Rehman Pezwak is a contemporary Dari/Persian poet of Afghanistan. He has attained a special place among his contemporary poets. He has not only a sung Persian poetry, but translated English and French verses as well. Although he follows the footsteps of classical poets but with a new ideas and motives. His poetical tone is similar to Khayyam’s Anacreontic verses and Hafez Sherazi’s narrative sonnets. His poetry have some rhetorical figures and cataphoric references. In this article his poetic resemblance has been highlighted with the said icons of the classical poetry. Also his lament poems which are the true image of environment, time and place with a captivating imagination has been discussed. Love, Happiness, idiolect, meiosis and dictions give him a picaresque character.